Environmental performance and financial performance : Evidence from manufacturing companies in Indonesia - Novy Fajriati (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Company with profit maximization oriented without caring about environmental and social impacts will cause a detrimental effect on society. This condition requires a concept namely green economy as a new paradigm in environmentally friendly economic development. This study aims to investigate the relationship between environmental performance and financial performance. This study used purposive sampling method that employs manufacturing companies between 2017-2021. Total sample of 240 firm-year observations data were analyzed in this study using regression approach. In this study, environmental performance measured by PROPER rating while financial performance measured by Return On Assets (ROA). This study reveals that average manufacturing companies achieve blue ratings which means the companies has managed the environment as required by laws and regulations The study finds that environmental performance significantly affects financial performance. Higher Environmental Performance leads to higher Financial Performance. This finding support stakeholders theory and legitimacy theory which states companies with good Environmental Performance will receive a positive response from stakeholders, and company’s involvement in PROPER could legitimize company’s activities in front of stakeholders which can enhance the company’s image. This research contributes to fills the gap in environmental performance and financial performance literature. This study provides a practical implication that the companies should to implement environmental performance practice as well in order to have higher financial performance.